Modulatory effect of dietary probiotic and prebiotic supplementation on growth, immuno-biochemical alterations, DNA damage, and pathological changes in E. coli-infected broiler chicks - Hashem, Mohamed A.; Hassan, Azza E. A.; Abou-Elnaga, Hala M. M.; Abdo, Walied; Dahran, Naief; Alghamdi, Ali H.; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2022)
Avian pathogenic Escherichia coli is one of the principal causes of heavy economic losses to the poultry industry. Little is known about the underlying mechanisms, particularly the potential role of immunoglobulin A and the DNA damage, involving the beneficial effects of dietary supplementation of probiotics and prebiotics in avian colibacillosis. The current study investigated the potential effects of probiotic and prebiotic dietary supplementation on E. coli-infected broiler chicks. A total of 120 1-day-old unsexed Hubbard chicks were divided into six groups: Group 1 was considered as a negative control; Group 2 was supplemented with 1 g/kg feed of Lactobacillus plantarum; Group 3 was supplemented with amylase enzyme; Group 4 served as a positive control infected orally by E. coli O78; Group 5 was supplemented with L. plantarum from 1-day-old chicken and then infected orally with E. coli O78; and Group 6 was supplemented with amylase enzyme from 1-day old chicken and then infected orally with E. coli O78. For all examined groups, the experimental period lasted for 42 days. The E. coli-infected group revealed a decrease in body performance parameters with a significant increase in the liver enzymes and renal function tests. The same group recorded a significant decrease in serum total proteins, albumins, and globulins, and the alteration of immunological parameters, antioxidant enzymes, oxidative stress parameters, and comet assay revealed highly damaged DNA in the liver and the intestine. By histopathological examination, a series of histopathological changes in the liver, the kidney, and the intestine were observed. The infected chick pretreated with probiotics or prebiotics demonstrated an improvement in body performance parameters besides a significant decrease in the hepatic enzymes and renal function tests. We noticed that, in treated groups, there was a significant increase in serum total proteins in the serum albumin and globulin levels, immunological parameters, and antioxidant enzymes. Furthermore, DNA damage and histopathological changes within hepatic, renal, and intestinal tissues were markedly diminished in the treated groups compared with the infected group. We concluded that the adverse effects of E. coli could be modulated through the chemopreventive administration of probiotics and prebiotics.